The Greatest Common Factor of the given expression should be that expression that can divide both. First, factor both expression,
x^4 = (x³)(x) and x³ = (x³)(1)
Therefore, both can be factored by x³. The answer is the third choice.
Answer:
15x - y = - 6.....15x + 6 = y...so we sub in 15x + 6 in for y on the other equation
5x - 3y = -13
5x - 3(15x + 6) = -13 <== the new equation
Step-by-step explanation:
-25x + 40
Step-by-step explanation:
-8 (4x-5) + 7x
-32x + 40 + 7x
-32x +7x + 40
-25x + 40
Answer:
7/13
Step-by-step explanation:
P(A or B) = P(A) + P(B) − P(A and B)
P(red or jack) = P(red) + P(jack) − P(red and jack)
P(red or jack) = 26/52 + 4/52 − 2/52
P(red or jack) = 28/52
P(red or jack) = 7/13